PRA DESAIN GEOMETRIK JALUR REL KELAS III RUTE MAJALENGKA KOTA BANDARA INTERNASIONAL JAWA BARAT - Firmansyah , Fikri; Susandy, Dony; Hendrayana , Yayat (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The construction of the Majalengka City–West Java International Airport (BIJB) rail line aims to improve connectivity and transportation efficiency, and support the growth of the Rebana and Kertajati Aerocity areas. Considering topography and potential population growth, rail was selected as a safe and sustainable mode of mass transportation. This research resulted in an optimal geometric design for the rail line, aligned with technical standards and local conditions. Methods included observation, literature review, and topographic data processing using Google Earth Pro, Global Mapper, and AutoCAD Civil 3D. Three alternative routes were evaluated for technical, social, environmental, and land requirements aspects, with alignment planning referring to Minister of Transportation No. 60 of 2012. The selected route design, 18.98 km long and with a design speed of 100 km/h, reduces travel time to less than 20 minutes, improves operational efficiency, and strengthens regional connectivity. The alignment consists of four horizontal curves in the Spiral–Curve–Spiral format and three vertical curves, adapted to the area's contours to ensure comfort, safety, and smooth operation.